Surgery for Chronic Pancreatitis. Issue 5 (July 2015) - Yang, Catherine J.; Bliss, Lindsay A.; Freedman, Steven D.; Sheth, Sunil; Vollmer, Charles M.; Ng, Sing Chau; Callery, Mark P.; Tseng, Jennifer F.
<x xml:space="preserve">Abstract</x> Objectives To examine if surgery performed for pain of chronic pancreatitis (CP) within 3 years diagnosis has greater odds of achieving complete pain relief than later surgery and to find optimal surgical timing for attaining pain relief in CP. Methods Retrospective review of records at a tertiary institution 2003 to 2011 for CP where the operative indication was pain. Outcomes were pain-free status, opioid use, and pancreatic insufficiency at 3-year follow-up. Univariate analysis by Fisher exact tests. Receiver operating curve to calculate cutoff threshold time for surgery. Results Outcomes for 66 patients were included. Median preoperative CP duration was 28 months (interquartile range, 12, 67). Twenty-six patients (39.4%) were free of pain at the 3-year follow-up. Thirty-four patients (51.5%) were opioid users at follow-up. Postoperatively, 34 patients (51.5%) demonstrated endocrine, and 32 patients (48.5%) demonstrated exocrine insufficiency. The optimal cutoff point for preoperative CP duration was 26.5 months (area under the curve, 0.66). Shorter duration of CP before surgery was a predictor of pain-free status and reduced postoperative opioid use at follow-up. Conclusions Results from a single institution analysis suggest early surgical intervention of 26.5 months or less of diagnosis is associated with improved pain control, and optimal timing for surgery may be earlier than previously thought.